Lessons down a rabbit hole: Alternate reality gaming in the classroom. (September 2014) - Chess, Shira; Booth, Paul
Alternate Reality Games can be used to reinforce classroom knowledge by encouraging collective learning practices and focusing on new media literacy skills. An Alternate Reality Game creates a game space from real-world locations by relying on information, both online and offline, to physically involve players in a game "space." While the majority of large Alternate Reality Games, to date, have been used as part of marketing campaigns, an increasing number of faculty teaching topics in digital media, technologies, and game studies have begun to employ the alternate reality game in the classroom. We argue that the affordances of Alternate Reality Games are best integrated within a "play-revise-design" format. By appropriating this emerging format in classroom spaces, we hope to teach students concepts such as new media literacies, the values of "safe failure, " and social learning, while giving students the tools for interactive storytelling.